Strategi Mendukung Perkembangan Anak Berkebutuhan Khusus Tuna Daksa Di SLB Negeri Keleyan Bangkalan - Mutiara Navy Putri S; Apriyanur Rohim; Irawati Irawati; Nurdiana Nurdiana; Andika Adinanda Siswoyo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to explore the supporting strategies implemented at the Keleyan Bangkalan State Special School in supporting the development of children with special needs and physical impairments. A qualitative approach was used in this research, with observation methods, in-depth interviews, and document study as data collection techniques. The research results show that supporting strategies include curriculum adjustments, development of physical and occupational therapy programs, and the use of special learning aids. Apart from that, the role of teachers and other supporting staff is very significant in providing motivation and emotional support to students. Collaboration with parents is also an important factor in ensuring continuity of support at home. This research concludes that a holistic approach involving academic, physical and emotional aspects is the key to facilitating optimal development of children with special needs and disabilities at the Keleyan Bangkalan State Special School. Recommendations are provided for further development of more comprehensive and sustainable support strategies.